Fantozzi perverso. Masochismo, desiderio inesausto e altre viziose amenità del ragioniere e dei congiunti (Schermi. Storie e culture del cinema e dei media in Italia, 2021)
Ugo Fantozzi, along with the co-stars of the serial movies and books dedicated to the popular Italian character, inhabits a world dominated by desire. This desire is sometimes expressed in sexual terms, but more often it takes on a desexualized, sadomasochistic tone. Sadomasochism as sexual sublimation in the Fantozzi saga also expresses the social dynamics of class domination devoted to expressing the asymmetries of the world represented in the works, specifically those of Italian society/labour of the final decades of the Nineteen century. In parallel with Fantozzi’s masochistic side, there is a sadistic one, belonging to the social reality in which he is embedded. Power relations in the saga are dominated by a Sadian libertine ruling class, which subjects its subordinates to their caprices, in a mere execution/demonstration/display of the anarchy of power. This vision is consistent with Paolo Villaggio’s deep, almost nihilistic distrust of the human race and especially of the contemporary Italian society in which he lived.